Antibacterial evaluation and preliminary phytochemical screening of selected ferns from Iran - M.B. Bahadori; F. Mahmoodi Kordi; A. Ali Ahmadi; Sh. Bahadori; H. Valizadeh (Iranian Society of Pharmacognosy, 2015)
Background and objectives: The main aims of this study have been finding out the antibacterial activity and preliminary phytochemical screening of some fern species. Methods: The antimicrobial activity of the methanol extracts of Polypodium interjectum Shivas, Polystichum woronowii Fomin, Polystichum aculeatum (L.) Roth., Dryopteris affinis (Lowe) Fraser-Jenk, Athyrium filix-femina (L.) Roth, Asplenium scolopendrium L., Asplenium adiantum-nigrum L. and Pteris cretica L., was screened by measuring the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against two Gram positive and Gram negative bacteria, Escherichia coli and Staphylococcus aureus, using standard assays. Besides, the phytochemical evaluation and measurement of the total flavonoid contents were also performed. Results: The maximum activity was exhibited by the extract of Dryopteris affinis with MIC value of 2 µg/mL. Polystichum aculeatum showed the same antibacterial potential against S. aureus. Some of the extracts had strong antibacterial activity (2-8 µg/mL) and others demonstrated moderate activity. Phytochemical analyses showed the presence of some important secondary metabolites in Iranian fern species. Triterpenoids and polyphenols were present in rhizome and aerial part of all plants. Total flavonoid contents range was 1.66 to 44.22 mg of catechin equivalents per gram of dry extract. Conclusion: Findings indicated that Iranian ferns have good antibacterial potential and could be a suitable source for antibiotic drug discovery.